THE EFFECTIVENESS OF SYNCHRONIZATION MANAGEMENT MODEL OF VOCATIONAL HIGH SCHOOL GRADUATE COMPETENCE WITH INDUSTRIAL COMPETENCY - Yudiono, Heri (The Journal of Educational Development, 2013)
This research aims to examine the effectiveness of the synchronization management of vocational high school graduate competence with industrial competency in mechanical major. It employed Research and Development (R & D) approach developed by Borg and Gall which was modified into three stages: (1) preliminary study; (2) development study; and (3) model dissemination. After testing its effectiveness using experimental design (before-after), the developed model was proven more effective than the old version. This insight leads positively to vocational graduate employment rate and competence improvement. Here, the stakeholders have a profound impact on model effectiveness as they assist and facilitate the synchronization process. It is recommended that their commitment or support shall reach its maximum capacity so that the vocational school graduate competence is well-matched to the demand from industry.